Capturing Prospective Geography Teachers' Self-Efficacy Beliefs towards Experimentation in Geography Classes: Presentation and Validation of a Measurement Instrument - Velling, Hanna; Schubert, Jan Christoph (Journal of Geography Education, 2023)
Teachers' self-efficacy beliefs play a central role in their classroom teaching, reason why there is need for instruments to capture them. This paper presents an instrument adapted from Physics Education for assessing self-efficacy beliefs towards experimenting in Geography. The paper also introduces the results of the validation process with initial Geography teacher education students (n=303). The results of confirmatory factor analyses, correlation and measurement invariance analyses, as well as mean value comparisons confirm the construct validity and reliability of the instrument. Concerning expression, the students show moderate to positive self-efficacy beliefs towards experimenting in Geography teaching.
Keywords: self-efficacy beliefs, experiments, prospective geography teachers, questionnaire, teacher behavior